Extracellular water compartment measured with the use of whole body and segmental bioimpedance technique in hemodialyzed patient - Małecka-Massalska, Teresa; Zubrzycki, Jarosław; Załuska, Wojciech; Książek, Andrzej (Polish Journal of Public Health, 2010)
Introduction. Monitoring of hydration levels in dialyzed patients is an important clinical aspect of the quality of treatment. Bioelectric impedance has been established as a valuable tool in the evaluation of hydration state. Aim. The aim of this study was to assess the differences in the sizes of the extracellular compartments measured with the use of two methods. Material and methods. The study was conducted with two methods: the whole body bioimpedance and segmental bioimpedance – WBIA and SBIA. Bioimpedance measurements were performed with a bioimpedance analyzer (model 4000B, Xitron Technologies, San Diego, CA, USA) with electrodes (7.7x1.9 cm²). Bioimpedance was measured in a logarithmic spectrum of 10 frequencies starting from 5 to 500 kHz. The readings were carried out for 10 chronically haemodialyzed patients, 5 females and 5 males aged between 33 and 69 years (average 41.5 years old) Results. In the study on differences between ECW values measured with the use of two methods – the whole body bioimpedance and segmental bioimpedance, statistically significant difference was detected both before and after the dialysis (t = -7.49; p = 0.0004 and t = 9.81; p0.05). Conclusion. The obtained results demonstrate that segmental body bioimpedance determining the hydration level in various parts of the body is a more precise tool in monitoring the hydrate status in hemodialyzed patients.